Tailored GuideLine Implementation in STrokE Rehabilitation (GLISTER) in Germany. Protocol of a Mixed Methods Study Using the Behavior Change Wheel and the Theoretical Domains Framework - Scheffler, Bettina; Schimböck, Florian; Schöler, Almut; Rösner, Katrin; Spallek, Jacob; Kopkow, Christian (Frontiers in Neurology, 2022)
Objective Evidence-based guidelines are important for informing clinical decision-making and improving patient outcomes. There is inconsistent usage of guidelines among physical therapists involved in stroke rehabilitation, suggesting the existence of a gap between theory and practice. Addressing the German guideline “evidence-based rehabilitation of mobility after stroke (ReMoS),” the aims of this project are (1) to describe the current physical therapy practice within the context of stroke rehabilitation in Germany, (2) to evaluate barriers and facilitators of guideline usage, (3) to develop, and (4) to pilot test a theory-based, tailored implementation intervention for the benefit of guideline recommendations. Materials and Methods This study uses a stepwise mixed methods approach for implementing a local guideline. A self-reported online questionnaire will be used to survey the current physical therapy practice in stroke rehabilitation. The same survey and systematic-mixed methods review will be used to evaluate the barriers and facilitators of guideline usage quantitatively. Semi-structured interviews will add a qualitative perspective on factors that influence ReMoS guideline implementation. The Behavior Change Wheel and Theoretical Domains Framework will be used to support the development of a tailored implementation intervention which will be pilot tested in a controlled study. Patient and physical therapy-related outcomes, as well as the appropriateness, such as acceptance and feasibility of the tailored implementation intervention, will be analyzed. Conclusion This will be the first endeavor to implement a guideline in German stroke rehabilitation with a focus on changing care provider behavior based on the knowledge of current practice and determining factors using a tailored and theory-based intervention.